Subjective Well-Being and Public Policy - Reto Odermatt; Alois Stutzer (Institute of Labor Economics (IZA), 2017)
Measures of subjective well-being have gained substantial attention in economics as quantitative approximations of individual welfare. They allow researchers to study relevant determinants of welfare on an individual as well as on a societal level. These determinants might not to be easily detectable in observable behavior. By referring to the recent well-being literature, we provide a selection of determinants of well-being that are important for public policy and show how the analysis of subjective well-being is applied as a complementary analytical tool for policy evaluation. We highlight the use of these measures for guiding public policy in areas that might involve suboptimal behavior. We also discuss some challenges for future research that are associated with the choice of evaluation metrics, the role of aspiration and adaption in evaluations, and utility misprediction.
Keywords: D61; D91; H4; I31; 330; subjective well-being; determinants of welfare; policy evaluation; bounded rationality